An ecological and methodological assessment of benthic gross primary production in northern lakes. Issue 3 (16th March 2022) - Puts, I. C.; Bergström, A.‐K.; Verheijen, H. A.; Norman, S.; Ask, J.
Abstract: Benthic gross primary production (GPP) is often the most important part of aquatic food webs in northern lakes, which are gradually warming and receiving increased terrestrial colored dissolved organic carbon loadings due to global change. Yet, measurements of benthic GPP are fairly uncommon, and methods and unit dimensions of benthic GPP are unstandardized and rarely compared. In this study, we measured benthic GPP in 27 headwater lakes from three regions in northern Sweden and analyzed potential constraining drivers of benthic GPP z rates at discrete depths and estimates of benthic GPP averages across the whole lake, as well as across the littoral zone. We also compared in situ measurements of benthic GPP averages across the whole lake with modeled values using the "autotrophic structuring model." We found that benthic GPP z rates were best explained by, and positively related to, available light (i.e., a function of depth and water color) and temperature. Benthic GPP averages across the whole lake, on the contrary, were best explained by the relative size of the littoral area, which is a measure that combines lake bathymetry and water color. The comparison between in situ measured and modeled estimates of benthic GPP averages across the whole lake revealed that (1) the autotrophic structuring model underestimates GPP at low values and overestimates GPP at high values compared with measured data, and that (2) measured values were related to temperature, which is not included as a variable in the autotrophic structuring model. Considering future predicted changes impacting northern latitude lakes, our results suggest that increased lake water temperatures can to some extent mitigate the negative impacts of reduced light availability from lake browning on benthic GPP z rates. The combined impact of these changes on benthic GPP averages across the whole lake will depend on, and be moderated by, lake bathymetry determining the relative size of the littoral area.